EKSEKUSI HAK TANGGUNGAN DI BANK SYARIAH PASCA UNDANG-UNDANG NOMOR 3 TAHUN 2006 - Suhaimi, Suhaimi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
The implications of Law No. 3 of 2006 on religious courts,  that the authority of the religious court expanded that includes Islamic economics were  showcased in Article 49, that the logical consequence aspects of constitutional courts religion to be the only court with jurisdiction  over issues  that occur  against Islamic economics , Writing in this thesis aims to know how the setting and execution of a security interest  in the post of Islamic Banks law No. 3 of 2006. In terms  of the types and  nature, this research includes the study of normative law, because it is done  from a juridical standpoint. The approach used  in this research is descriptive analysis, the authors describe all the existing materials and then analyze the content analysis  method. From  the  research found  that  setting  the  execution of Responsibility  Rights in Islamic  banks is through  the religious court  and  use  the settings  general  civil law and  the execution of Responsibility  Rights in Islamic banks initiated by filing a subpoena in a religious court so that the court religion did session aan maning  form of reprimand against  customer default  to meet its obligations  as an Islamic  bank  customers, and  than  if customers do not do it next Islamic banks  apply for the execution of Responsibility Rights to the customer. Head of religious courts provide execution Responsibility  Rights determination to further  instruct  the  religious  court  bailiff accompanied by two  witnesses to the execution of the seizure of the object. Then notified of the seizure to all agencies associated with the land and the buildings on it were  confiscated